2018
DOI: 10.1002/lary.27589
|View full text |Cite
|
Sign up to set email alerts
|

Airway anomalies in patients with craniosynostosis

Abstract: Objectives: 1) Characterize the spectrum of airway anomalies in patients with craniosynostosis, and 2) identify clinical characteristics of these patients that may be associated with the development of airway anomalies.Methods: This study is a retrospective case series assessing the type and frequency of airway anomalies in all patients with craniosynostosis seen at a tertiary-care children's hospital between 2000 and 2016. Cohort analyses were then performed to identify differences in airway anomalies depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…This present study determined that patients with craniosynostosis, especially syndromic patients, had a significantly higher incidence of not only choanal atresia but also other various airway anomalies. These results are consistent with a single institution retrospective review of syndromic craniosynostosis patients by Matthews et al 3 which found that patients with syndromic types were at a much higher risk of developing these anomalies. For example, they similarly discovered higher rates of subglottic stenosis and tracheomalacia in those with syndromic craniosynostosis 3 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This present study determined that patients with craniosynostosis, especially syndromic patients, had a significantly higher incidence of not only choanal atresia but also other various airway anomalies. These results are consistent with a single institution retrospective review of syndromic craniosynostosis patients by Matthews et al 3 which found that patients with syndromic types were at a much higher risk of developing these anomalies. For example, they similarly discovered higher rates of subglottic stenosis and tracheomalacia in those with syndromic craniosynostosis 3 …”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a single institution retrospective review of syndromic craniosynostosis patients by Matthews et al 3 which found that patients with syndromic types were at a much higher risk of developing these anomalies. For example, they similarly discovered higher rates of subglottic stenosis and tracheomalacia in those with syndromic craniosynostosis 3 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(10) Some of the causes are associated with some syndromes. (11) There are very few case series in Indian population reporting such cases. In our tertiary care centre, we come across many cases with stridor.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%